Incidence of Acute Renal Failure in Full Term Neonates with Birth Asphyxia - Jha, Chandra Bhushan; Tamrakar, Akhil (Birat Journal of Health Sciences, 2019)
Introduction: Birth asphyxia is an eventuality having far reaching consequences in the neonatal period. Hypoxia and ischemia can cause damage to almost every tissue and organ in the body and various target organs involved. Renal insult is a recognized complication of birth asphyxia and carries a poor prognosis. Timely detection of renal dysfunction and appropriate management may favorably alter the prognosis in many neonates with birth asphyxia.Objective: The present study was done to find out the incidence of acute renal failure in the full term neonates with birth asphyxia.Methodology: A cross sectional study was conducted at Birat Medical College Teaching Hospital, Morang, Nepal from 1st September 2017 to 28th February 2018. Fifty full term neonates born with Apgar score of 1.5gm/dl or urine output